2015
DOI: 10.1371/journal.pone.0124668
|View full text |Cite
|
Sign up to set email alerts
|

Higher Body Mass Index Increases the Risk for Biopsy-Mediated Detection of Prostate Cancer in Chinese Men

Abstract: ObjectiveTo investigate the relationship between body mass index (BMI) and prostate cancer (PCa) risk at biopsy in Chinese men.Patients and MethodsWe retrospectively reviewed the records of 1,807 consecutive men who underwent initial multicore (≥10) prostate biopsy under transrectal ultrasound guidance between Dec 2004 and Feb 2014. BMI was categorised based on the Asian classification of obesity as follows: <18.5 (underweight), 18.5–22.9 (normal weight), 23–24.9 (overweight), 25–29.9 (moderately obese), and ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
0
14
1
Order By: Relevance
“…One recent study considered the fact that BMI values in Asians are lower than in Western counterparts and thus used a BMI cut-off of 25 kg/m 2 to define obesity. In doing so, they found that higher BMI was linked with increased risk of PCa at biopsy, however no significant association was seen between obesity and HGPCa8. A recent report also found that Asian men with a BMI ≥25 kg/m 2 were at a higher risk of having PCa at initial biopsy9, confirming that indeed obesity may be associated with higher risk of total PCa, although the associations between obesity and PCa grade among Asian men are still unclear.…”
mentioning
confidence: 97%
“…One recent study considered the fact that BMI values in Asians are lower than in Western counterparts and thus used a BMI cut-off of 25 kg/m 2 to define obesity. In doing so, they found that higher BMI was linked with increased risk of PCa at biopsy, however no significant association was seen between obesity and HGPCa8. A recent report also found that Asian men with a BMI ≥25 kg/m 2 were at a higher risk of having PCa at initial biopsy9, confirming that indeed obesity may be associated with higher risk of total PCa, although the associations between obesity and PCa grade among Asian men are still unclear.…”
mentioning
confidence: 97%
“…This observation is consistent with previous reports utilizing immunohistochemistry 18 and FACS. 19 Increased BMI is considered as a strong and independent predictor of obesity- | 645 associated comorbidities, [19][20][21] including asthma. 22,23 In several other disease states, the negative end-organ effects of obesity are recognized to be a consequence of higher pro-inflammatory activity of the visceral fat depot, compared to the subcutaneous fat depot, 24 with ATMs having a pivotal role.…”
Section: Atms In Obese Asthmatics Vs Non-asthmaticsmentioning
confidence: 99%
“…The prevalence of prostate cancer differs from one country to another due to coverage of prostate-specific antigen screening [ 2 ]. In China, the rate of prostate cancer is rapidly increasing and especially in patients with obesity or diabetes [ 3 , 4 ]. As androgen receptor plays an important role in the pathogenesis of prostate cancer, androgen-deprivation therapy remains the principal method for treatment of patients with prostate cancer [ 5 ].…”
Section: Introductionmentioning
confidence: 99%